Plants : A Very Short Introduction - Walker, Timothy, 1958- (Oxford, New York Oxford University Press, 2012)
"Plants form a fundamental element of the biosphere, and the evolution of plants has directly affected the evolution of animal life and the evolution of the Earth's climate. Plants have also become essential to humans not only in the form of cereal crops, fruit, and vegetables, but in their many other uses in wood and paper, and in providing medicines. In this Very Short Introduction Timothy Walker, Director of the Botanical Gardens in Oxford, provides a concise account of the nature of plants, their variety and classification, their evolution, and their aesthetic and practical value, stressing the need for their conservation for future generations"--The publisher.
Include Index and Illustration
Keywords: Plants -- Botany